Estrategias Comunicativas Digitales Del Paisaje Cultural Cafetero Colombiano En El Municipio De Armenia (2013)
The incorporation of the cultural coffee landscape in the list of UNESCO’s world heritages, allows that this investigation should focus in that the citizens know what is a cultural coffee landscape and acquire sense of belonging for the same one. For such a reason it is important to analyze the content of the web pages that include to the cultural coffee landscape in his contents; identifying digital strategies of communication rested on videos, photographies and texts. The incorporation of the points of view of the different social actors and his participation in the promotion of the development, it’s indispensable for the social construction and the sustainability of the Cultural Coffee Landscape